2022
DOI: 10.1021/acs.macromol.2c01843
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Topological Barriers on the Crystallization Behavior of Ring Polyethylene Melts with Trefoil Knots

Abstract: Topological barriers in ring polyethylene (PE) melts of trefoil knots inhibit crystallization due to self-entanglement, as confirmed by united atom molecular dynamics (UAMD) simulations. In this study, we clarified the decrease in the topological barriers of self-entangled knots with increasing polymer chain length (N) and the localization of the knotted segments in the noncrystallized region. In the UAMD simulations, isothermal crystallization processes were performed at T = 300 K for the trefoil knots using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…16 Hagita et al indicated that the shortened segment of a knot in a ring polymer hinders crystallization, and this retardation vanishes with the increase of chain lengths. 17 A trefoil knot is the simplest nontrivial knot projected on a plane with the minimum three crossings. 18 Molecular simulations have demonstrated that the trefoil knots are dominant among the various kinds of topological intrachain knots in polymer single chains 19−21 as well as in melt chains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Hagita et al indicated that the shortened segment of a knot in a ring polymer hinders crystallization, and this retardation vanishes with the increase of chain lengths. 17 A trefoil knot is the simplest nontrivial knot projected on a plane with the minimum three crossings. 18 Molecular simulations have demonstrated that the trefoil knots are dominant among the various kinds of topological intrachain knots in polymer single chains 19−21 as well as in melt chains.…”
Section: Introductionmentioning
confidence: 99%
“…During polymer crystallization, the topological constraints of intrachain knots and interchain entanglements will influence the conformational changes of flexible long-chain polymers. So far, the constraint effects of interchain entanglement on polymer crystallization have been extensively investigated, but the constraint effects of intrachain knots on polymer crystallization received little attention. De Gennes proposed that crystallization will reel in the chain and thus tighten the knots . Saitta and Klein reported that the knots enhance local density fluctuations for intramolecular crystal nucleation during stretching of a single polymer chain .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation